Relation between sweet food consumption and liking for sweet taste in French children. (March 2017) - Divert, C.; Chabanet, C.; Schoumacker, R.; Martin, C.; Lange, C.; Issanchou, S.; Nicklaus, S.
Highlights: Relationship between sweet food consumption and sweetness liking in children. Assessment of liking for three matrices varying in sucrose content. Estimating sweet food consumption with frequency of consumption and sweetness intensities. No clear association between sweet food consumption and sweetness liking was observed. Abstract: Given the growing evidence that sugar intake could promote a positive energy balance and lead to weight gain and obesity, the World Health Organization published new recommendations in terms of sugar consumption in children and adults. However, the influence of sweet food and drink consumption on sweetness liking has not been fully characterized. Therefore, the present study aimed at exploring whether sweet food consumption is positively associated with sweetness liking in 101 children aged between 7 and 12 years. Sweetness 'preference' and liking optima for sweetness (calculated for 100% and 60% of the children, respectively) were measured by asking the children to taste and rate on a 9-point hedonic scale three ranges of food products that varied in sucrose content. Each range of products (sugar water, strawberry syrup with water, and cornflakes in milk) contained 5 levels of sweetness. Sweet food consumption from sweet drinks, candies and snacks, cereal/dairy/fruit products or added sugar were calculated using data from a food frequency questionnaire which focused on the children's consumption of sweet products, taking into account the sweetness intensity of each food. Structural Equation Modelling fitted for the 101 children showed a weak but significant positive association between candy and snack consumption and sweetness liking (path coefficient = 0.28; p = 0.04). However, sweetness liking was not associated with sweet drink consumption, cereal/dairy/fruit product consumption or added sugar consumption. The absence of a clear relationship between sweet food consumption and sweetness liking in this sample calls for further clarifications on the potential effect of sweet food consumption on preferred sweetness level in liquid and solid foods.